Purveyors of fine halos: II. Chemodynamical association of halo stars with Milky Way globular clusters - Hanke, Michael; Koch-Hansen, Andreas; Prudil, Zdeněk; Grebel, Eva K.; Bastian, Ulrich (Astronomy and astrophysics, 2020)
A long-lasting open question in the field of Galactic archeology refers to the size of the contribution from former globular cluster (GC) stars to the formation of the stellar halo of the Milky Way. We contribute to answering this important question by establishing observational links between the present-day halo field star population and GCs. To this end, we combined astrometric information such as space motions and parallaxes from the second data release of the Gaia mission (Gaia DR2) with spectroscopic radial velocities and metallicities ([Fe/H]) from the Sloan Digital Sky Survey (SDSS-IV, DR14) to end up with a seven-dimensional chemodynamical information space for more than 3 × 105 stars. Moreover, from our previous study, we incorporated the sample of halo giant stars with a distinct chemical signature (strong CN bandheads) that resembles the light-elements anomaly otherwise only seen in the second generation of globular cluster stellar populations. Using three different tagging techniques - among which is the exploration of conservative integrals of motion - we are able to establish unique associations between 151 extratidal stars in the neighborhood of eight GCs, which coincide with earlier findings of stellar envelopes beyond the tidal radius and even beyond (out to several tens of tidal radii). In addition, we trace the possible origin of about 62% of the sample of CN-strong giants to their potential host clusters. We find a connection between several of the involved GCs and the Gaia-Enceladus and Sequoia merger events. By establishing kinematic and chemical connections between 17 CN-strong stars and their surrounding fields, we identify co-moving groups of stars at the same [Fe/H] with a possible cluster origin. Some of these associations contain RR Lyrae variables, which allows meaningful distance inferences to be made. From these, we find strong evidence that four CN-strong stars and their associates are connected to the Sagittarius stream whilst their tightly confined [Fe/H] may hint to a birth site in M 54, the massive cluster in Sagittarius’ core remnant. Finally, by employing the counts of CN-strong and bona-fide CN-normal giants from our novel sample, we provide tentative estimates for the fraction of first-generation cluster stars among all stars lost to the halo. In the immediate cluster vicinity, this value amounts to 50.0 ± 16.7% while the associations in the halo field rather imply . We speculate that - if proven real by spectroscopic follow-up - the disparity between these numbers could indicate a major contribution of low-mass clusters to the overall number of stars escaped to the halo or could alternatively suggest strong mass loss from the first generation during early cluster dissolution.
Gesehen am 18.03.2021